The influence of influence: the effect of task repetition on persuaders and persuadees - Chesney, Thomas; Chuah, Swee-Hoon; Hoffmann, Robert; Larner, Jeremy (Elsevier, 2017)
We investigate how the experience of influencing and of being influenced impacts on a subsequent, immediate attempt to influence and be influenced. We conduct an experiment using participant dyads matched in a round-robin design which systematically measures the influence one individual has on another in a decision task using a short, anonymous, computer mediated, text based exchange. Findings show that being influenced in a round of the task tends to be positively related to being influenced in the subsequent two rounds with the effect weakening each time. We find no impact on the ability to influence.